Design of a Sky Camera-Based Cloud Monitoring Camera at the Agam Space and Atmospheric Observation Station, Bukit Kototabang - Syafrijon, Syafrijon; Fahmi Rahmatia; Ridho Pratama; Teguh Nugraha Pratama; Ednofri; Muzirwan; Ismail, Ainaa Maya Munira binti Ismail (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Indonesia is a center of convection and acts as a driving force for global atmospheric circulation due to its geographical position. Moreover, Kototabang Hill is one of the national strategic areas in the equatorial atmospheric observation room with limited cloud cover data so that tools and development are needed to meet these data needs. Sky Camera for the purpose of observing clouds (Cloud Camera) is urgently needed to complement the need for cloud cover data to support observation and research activities in the field of the atmosphere. The Cloud Camera design is done by modifying the CCD Camera with several supporting devices including fish eye, solar tracker, sun filter and dome. Evaluation of the urgency of these enhancements is discussed in this paper. Among the four combinations of using supporting instruments (dome and sun filter) for the Cloud Camera device, the best image obtained is the device that uses a sun filter and without a dome. Among the four combinations of using supporting instruments (dome and sun filter) for the Cloud Camera device, the best image obtained is the device that uses a sun filter and without a dome.